Interactions Between an Apex Predator and Mesopredators Across a Landscape with Human Interference - Zanón Martínez, Juan Ignacio (2022)
Human activities have populated the planet with domestic animals like livestockwhile also eliminating wild species that could conflict with them. We investigatedfactors affecting predator occurrence in semiarid landscapes of centralArgentina and tested for evidence of mesopredator release at large scales. Ourstudy region has a few, small protected areas interspersed within a mosaic of livestockranches and game hunting grounds. We hypothesized that mesopredatorswould avoid spatial and temporal overlap with the apex predator, the puma, butthat human activities (i.e., cattle raising and trophy hunting) would dampen top-downeffects and mediate habitat use of smaller carnivores.